Research on Halal Certification in Indonesia - Akmal (Journal of Islamic Economics Literatures, 2021)
Guaranteed halal products in Indonesia have been equipped with adequate regulatory tools, starting from the Law to the Regulation of the Minister of Religious Affairs. Unfortunately, the halal certification process has not been running as it should be. The growing public awareness of halal and business actors’ enthusiasm regarding halal certificates did not appear to be supported by the organization’s readiness and good halal governance. This study aims to determine the developing map and trend of halal certification published by reputable journals. The data were analyzed from more than 55 indexed research publications. The export data is then processed and analyzed using the R Biblioshiny application program to determine the bibliometric map of halal certification research. The result shows that the number of publications on the development of halal certification in Indonesia has increased significantly. The most popular keyword topics are halal, product, and Indonesia. Based on the literature, there are at least 4 aspects of the problem of implementing halal certification in Indonesia, namely: infrastructure aspect, technical, regulatory and inter-relational aspects.